MicroRNA cerebrospinal fluid profile during the early brain injury period as a biomarker in subarachnoid hemorrhage patients - Pedrosa, Leire; Hoyos, Jhon; Reyes, Luis; Llull, Laura; Santana, Daniel; de Riva, Nicolás; Mellado, Ricard; Sala, Xavier; Rodríguez-Hernández, Ana; Enseñat, Joaquim; Amaro, Sergio; Torné, Ramon (Frontiers in Cellular Neuroscience, 2022)
Delayed cerebral ischemia (DCI) is a dreadful complication present in up to 30% of patients with spontaneous subarachnoid hemorrhage (SAH). Indeed, DCI is one of the main causes of long-term disability in SAH, yet its prediction and prevention are troublesome in poor-grade SAH cases. In this prospective study, we explored the potential role of micro ribonucleic acid (microRNA, abbreviated miRNAs), – small non-coding RNAs involved in clue gene regulation at the post-transcriptional level – as biomarkers of neurological outcomes in SAH patients. We analyzed the expression of several miRNAs present in the cerebrospinal fluid (CSF) of SAH patients during the early stage of the disease (third-day post-hemorrhage). NanoString Technologies were used for the characterization of the CSF samples. We found an overexpression of miRNAs in the acute stage of 57 SAH in comparison with 10 non-SAH controls. Moreover, a differential expression of specific miRNAs was detected according to the severity of clinical onset, but also regarding the development of DCI and the midterm functional outcomes. These observations reinforce the potential utility of miRNAs as prognostic and diagnostic biomarkers in SAH patients. In addition, the identification of specific miRNAs related to SAH evolution might provide insights into their regulatory functions of pathophysiological pathways, such as the TGF-β inflammatory pathway and blood-brain barrier disruption.